Telling their own stories: Encouraging veterinary students to ethically reflect. (23rd March 2021) - Hobson‐West, Pru; Millar, Kate
Abstract : Background: Veterinary practice raises complex and unique professional ethical dilemmas. There is increasing discussion of how best to deliver ethics education to veterinary students, so that they are fully prepared to address ethical conflicts in professional practice. This paper proposes the use of innovative methods to allow students to share and reflect on their own experiences of ethical dilemmas. Methods: Two innovations are described. The first is formal and compulsory, and involves a small‐group facilitated session for final year students, wholly designed around student dilemmas. The second is informal and voluntary, and constitutes a short‐story writing competition. Results: The methods described are conducive to student engagement in ethics and ethical reflection. Conclusion: Veterinary schools should consider adopting student‐led techniques, deliberately designed to allow students to tell their own stories. Similar methods could also be adapted for use in clinical practice, thereby creating opportunities for professional dialogue on ethical dilemmas.